2006
DOI: 10.1016/j.cell.2006.07.033
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1 Activation of Lipid Metabolic Pathways in Response to Bacterial Pore-Forming Toxins Promotes Cell Survival

Abstract: Many pathogenic organisms produce pore-forming toxins as virulence factors. Target cells however mount a response to such membrane damage. Here we show that toxin-induced membrane permeabilization leads to a decrease in cytoplasmic potassium, which promotes the formation of a multiprotein oligomeric innate immune complex, called the inflammasome, and the activation of caspase-1. Further, we find that when rendered proteolytic in this context caspase-1 induces the activation of the central regulators of membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
423
3
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 461 publications
(448 citation statements)
references
References 57 publications
19
423
3
3
Order By: Relevance
“…Infection with A. hydrophila induces caspase-1 activation, IL-1b release and pyroptosis It has been reported that aerolysin produced by A. salmonicida induces caspase-1 activation in CHO cells [20,21]. However, whether whole bacterial infection by A. hydrophila leads to caspase-1 activation in macrophages has not been elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Infection with A. hydrophila induces caspase-1 activation, IL-1b release and pyroptosis It has been reported that aerolysin produced by A. salmonicida induces caspase-1 activation in CHO cells [20,21]. However, whether whole bacterial infection by A. hydrophila leads to caspase-1 activation in macrophages has not been elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…1). This latter finding further supports our notion that A. hydrophila also induces caspase-1-independent cell death.Caspase-1 activation is mediated by aerolysin, HlyA and multifunctional RtxA Purified aerolysin has been shown to induce caspase-1 activation and an aerolysin-deficient A. trota mutant was incapable of inducing caspase-1 activation in human fibroblasts [21]. However, an A. hydrophila aerolysin mutant (DaerA) remained capable of activating caspase-1 and IL-1b processing/secretion in infected BMM (Fig.…”
mentioning
confidence: 96%
“…Our results indicate that pore formation by HlyA in the membrane of target bladder epithelial cells is required to inactivate Akt. Pores formed by HlyA stimulate both Ca 2ϩ fluxes and decreases in cytosolic K ϩ levels, events that can significantly affect cellular signaling processes (Uhlen et al, 2000;Gurcel et al, 2006). However, changes in intracellular Ca 2ϩ or K ϩ concentrations did not seem to affect HlyA-mediated inactivation of Akt.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the processing of pro-IL-1b/IL-18 and induction of pyroptosis, caspase-1 has been shown to support the survival of cells in response to membrane damage caused by pore-forming toxins derived from invasive bacteria (Gurcel et al 2006). In response to stimulation with aerolysin from Aeromonas hydrophila, caspase-1 is activated by K ?…”
Section: Membrane Stabilizationmentioning
confidence: 99%